Relationship Between Critical Thinking Skills and Students' Decision-Making Skills on Virus Materials In MAN 1 Tasikmalaya - Lutfia Fajriah; Endang Surahman; Romy Faisal Mustofa (Mangifera Edu, 2021)
This research aims to find out the relationship between critical thinking skills and students' decision-making skills on viral material in MAN 1 Tasikmalaya Regency. The research method used is correlational. The population in this study was all students of class X MIPA consisting of 8 classes. The sampling technique uses purposive sampling with samples class X MIPA 3, X MIPA 4, and X MIPA 5 with 107 students. Data collection techniques using instruments in the form of tests. The research instrument used in this study consists of two instruments, namely critical thinking skills instruments in the form of a question in the form of a description, as many as ten questions with five indicators. For the instrument of decision-making skills in the form of a question in the form of a description, as many as 12 questions with five indicators. The data analysis technique used is a bivariate correlation test. Based on the results of research shows that critical thinking skills have a weak relationship with decision-making skills. This is evidenced by a correlation coefficient value of 0.208 with a determination coefficient value of 4.3%. Keywords: Critical Thinking Skills, Decision Making Skills, Virus Material.